Association of Birth Preparedness and Place of Delivery among the Mothers - Chaudhary, Om Prakash; Poudyal, Jiwan; Shah, Rajani; Upadhyay, Hari Prasad; Parajuli, Sumitra; Sedain, Prativa (International Journal of Silkroad Institute of Research and Training, 2023)
Background: Birth preparedness saves women’s lives and health through planning and preparation for delivery. The objective of this research is to find the practices of birth preparedness and its association between selected variables. Methods: Analytical cross-sectional study was conducted in Garuda Municipality among168 mothers using interview techniques. Statistical Package for the Social Sciences (SPSS) was used for analyzing the data, chi-square test was done. Results: Only (14.3%) of respondents had knowledge and practice of birth preparedness . That the distribution of independent variables. Among the education of respondents (P=0.008), number of children (P=0.025), ANC by protocol (0.011), counseling during ANC checkup (P<0.001), birth attendant (<0.001), knowledge of intensive (<0.001) had significant association with place of delivery. Conclusions: Education of mother, education of husband, number of children, ANC by protocol, counseling during ANC checkup, knowledge of danger signs requiring checkup in pregnancy, final decision maker, birth attendant and knowledge of intensive were significantly associated but other socio-demographic fac-tors such as mother’s age, religion, type of family, caste, occupation of mother as well as practice of Birth Preparation